Healthcare Chaplains Among the Virtues? - Newitt, Mark (Practical theology, 2016)
Noting that the bearing and presence of a chaplain in being with bereaved parents is as important as the provision of liturgy and ritual, this article argues that chaplaincy would benefit from an engagement with virtue ethics. The article begins by suggesting that many of the situations a chaplain encounters are too complex for principle based ethical approaches and outlines the merit of a virtue-based approach. As part of this the concept of a regulative ideal, as a way to understand how character regulates decision making, is discussed and engendering an encounter with hope proposed as a regulative ideal for chaplains supporting bereaved parents. Following this, the article proposes three virtues - attentiveness, openness and probity - as being key to the character of a chaplain. Finally, the article supports the call for case studies of chaplaincy work and argues for greater use of mentoring and shadowing within chaplaincy.